Enzimas lisossomais em células renais em cultura submetidas a condições que mimetizam o estado diabético - Peres, Giovani Bravin [UNIFESP] (2016)
Diabetic nephropathy affects about one third of ali diabetic patients, and is the most common cause of end-stage renal disease. By the use of intravital microscopy and fluorescent albumin, it has been shown that the renal filtration of albumin in normal rats is almost 50 times the values previously reported, obtained by micropuncture. As the albumin concentration in normal urine is very low, it seems that there is a retrieval pathway, possibly in proximal tubular cells. Internalized albumin may either be retrieved back to circulation via transcytosis or follow Iysósomal degradation, with fragments being exocytosed back into tubular lumen and excreted in urine. So, increased albuminuria in diabetic patients could be due to lower renal degradation rates of albumin. We have recently reported decreased expression and activities of Iysosomal proteases, especially cathepsins B and L, in kidney during the early stages of diabetes (10 and 30 days) in rats. Important morphological changes were observed in proximal tubules, which have lost their brush borders and presented thinner walls, in comparison to normal. Immunohistochemistry have shown that most of cathepsin B is localized in proximal tubular cells, suggesting that these cells are implicated in the early stages of the disease. Despite ali this information concerning Iysosomal enzymes and diabetes, the mechanisms that trigger these changes are unknown. The aim of the present study was to investigate the effects of high glucose and advanced glycation end products (AGEs) upon Iysosomal enzymes in kidney cells. Immortalized cell lines derived from kidney cells were submitted to conditions that mimic the diabetic state - high glucose and/or AGE-albumin (AGE-BSA) - and their effecfs upon cell proliferation, expression and activities of Iysosomal enzymes, and expression of other mediators of inflammation and cell metabolism were studied. The results have demonstrated that high glucose increased the proliferation rates of mesangial cells only (CMHI), while epithelial tubular cells were not affected. Although control-BSA had no effect upon the proliferation rate of the cells here studied, AGE-BSA caused a marked decrease in the number of both epithelial and mesangial cells, in a dose-dependent fashion, irrespectively of glucose concentration in culture medium Concerning Iysosomal enzymes, the main cysteine-protease in ali the renal-derived cells here studied was cathepsin B, although its concentration was much lower in mesangial than in epithelial cells. Exposure to high glucose had no effect on the activity of the enzyme, but AGE-BSA caused a marked decrease in LLCPK only, while increases were observed in the other cell lines. Furthermore, the levels of nitric oxide (NO) produced and secreted to the culture media were also increased by AGE-BSA in ali cell types here studied, suggesting oxidative stress. Concerning the expression of some proteins, Western blotting has shown that, among the investigated proteins, the mammalian (mechanistic) target of rapamycin - mTOR - was the most significantly affected by exposure to AGE-BSA.